Recherche et pratique : sensibiliser les enseignants en école professionnelle aux dimensions identitaires négociées dans l’interaction - Barbara Duc (Communiquer)
This contribution concerns interventions in the framework of continuing education of training college teachers in Switzerland. These interventions lean on an interactional research led in initial vocational education and training programs. It is a study that aims at better understanding how apprentices’ trajectories of training are built through the interactions in which they participate in school or in the work place. By working on sequences of audio-video data through the use of analytical tools coming from interactional and multimodal linguistics, the participants in the training are made aware of what is at stake in communication in class, and particularly of the identity dimensions negotiated in interaction. To come back to these interventions, from their conception to their implementation, allows questioning the way they can serve training. More generally, our reflections concern the relation between research and practice.